The Little Data Book on Financial Inclusion 2018 - World Bank (World Bank, Washington, DC, 2018)
The Little Data Book on Financial Inclusion 2018 is a pocket edition of the Global Findex database published in 2018. The data represent a third round of data collection since the Global Findex database was launched in 2011. The database provides nationally representative, demand-side data on access to and use of accounts, credit, payments, and savings by adults age 15 and above in 144 economies. In addition, new indicators measure how people make or receive digital payments. This book presents data for selected indicators by country, region, and income group. For some indicators the data are disaggregated by gender, income level, employment status and rural residence. This third edition of the database was compiled in 2017 and includes updated indicators on access to and use of formal and informal financial services and additional data on financial technology, or fintech, including the use of mobile phones and the internet to complete financial transactions.